Mitochondrial Quality Control: Decommissioning Power Plants in Neurodegenerative Diseases. (28th October 2013) - Mukherjee, Rukmini; Chakrabarti, Oishee
Abstract : The cell has an intricate quality control system to protect its mitochondria from oxidative stress. This surveillance system is multi-tiered and comprises molecules that are present inside the mitochondria, in the cytosol, and in other organelles like the nucleus and endoplasmic reticulum. These molecules cross talk with each other and protect the mitochondria from oxidative stress. Oxidative stress is a fundamental part of early disease pathogenesis of neurodegenerative diseases. These disorders also damage the cellular quality control machinery that protects the cell against oxidative stress. This exacerbates the oxidative damage and causes extensive neuronal cell death that is characteristic of neurodegeneration.